Study of a Conformational Equilibrium of Lisinopril by HPLC, NMR, and DFT - Sondes Bouabdallah; Med Thaieb Ben Dhia; Med Rida Driss (International Journal of Analytical Chemistry)
The isomerization of lisinopril has been investigated using chromatographic, NMR spectroscopic, and theoretical calculations. The NMR data, particularly the NOEDIFF experiments, show that the major species that was eluted first is the trans form. The proportion was 77% and 23% for the trans and cis, respectively. The thermodynamic parameters (ΔH, ΔS, and ΔG) were determined by varying the temperature in the NMR experiments. The interpretations of the experimental data were further supported by DFT/B3LYP calculations.